Efficient nanostructured heterogeneous catalysts by electrochemical etching of partially crystallized Fe-based metallic glass ribbons. (20th January 2021) - Zhang, Qiaoyue; Liang, Shun-Xing; Jia, Zhe; Zhang, Wenchang; Wang, Weimin; Zhang, Lai-Chang
Highlights: Nanoporous structure was synthesized by electrochemical etching. Fe2 B phase was selectively dissolved by electrochemical etching. More surface active sites were exposed after electrochemical etching. Etched ribbon had 2 times higher catalytic efficiency than as-annealed composite counterpart. Abstract: Although an increasing interest has been attracted to further develop heterostructured catalysts from metallic glasses (MGs) by heat treatment, overcoming surface oxidation effect is still a critical problem for such environmental catalysts. Herein, a short-time electrochemical etching of partially crystallized Fe-based ribbons in 0.3 M H3 PO4 electrolyte enables the formation of honeycomb-like nanoporous structure as effective catalytic active sites in Fenton-like process. Studies of structure and surface morphologies reveal that the formation of nanoporous structure by potentiostatic etching originates from electrochemical potential difference of nanocrystals (α-Fe (Si) and Fe2 B) and residual amorphous phase in partially crystallized ribbons, where Fe2 B having a lower open circuit potential tends to be selectively dissolved. Simultaneously, thin oxide layer after electrochemical etching exposes more active sites for H2 O2 activation and provides an effective protection of nanocrystals from massive loss during etching. Investigation of optimal processing conditions suggests that the selection of electrolyte plays an important role; dye degradation rates of etched ribbons in HNO3 and Na2 SO4 electrolytes can also achieve at least 2 times higher than that of as-annealed ribbons. This work holds the promise to develop novel environmental catalysts by effective electrochemical etching of partially crystallized ribbons.